Calibration of Polytomous Response Mathematics Achievement Test Using Generalized Partial Credit Model of Item Response Theory - Ayanwale, Musa Adekunle (EDUCATUM Journal of Science, Mathematics and Technology, 2021)
This study assessed the empirical comparability of item calibration in the developed essay (DEVessay-MAT) iand (NECOessay-MAT) iimathematics iiachievement iitest iiunder iithe iiGeneralized iiPartial iiCredit iiModel i(GPCM). The iiiinstrumentation iiiresearch iiiapproach iiiof iiicounterbalance iiidesign iiiwas iiiemployed. iiiThe iiisample consisted iiiof iii1080 iiisenior iiisecondary iiischool iiistudents iii(SSS3) iiiof iii36 iiischools, iiiwho iiiwere drawn randomly iiifrom iiiOsun iiiEast iiisenatorial iiidistrict iiiof iiiOsun iiiState, iiiNigeria. iiiTwo iiiinstruments iiiwere used iiiand iiidata iiiobtained iiiwere iiisubjected iiito iiiParallel iiiAnalysis iii(PA), iiiGeneralized iiiPartial iiiCredit Model iii(GPCM) iiiand iiiIndependent iiisample iiit-test. iiiResults iiishowed iiithat iiithe iiitest iiidoes iiinot violate unidimensionality iiiwith iiithe iiifirst iiiEigenvalue iii(2.05) iiifrom iiithe iiiexperimental iiidata iiiwas iiigreater than iiithe iiifirst iiirandom iiiEigenvalue iii(1.17) iiifrom iiiPA, iiiwhile iiiother iiiEigenvalues iiifrom iiithe experimental iiidata iiiwere iiiless iiithan iiithe iiirest iiiof iiiEigenvalues iiiunder iiiPA. iiiAlso, iiithere iiiexisted iiia significant iiidifference iiibetween iiithe iiistep iiidifficulties/overall iiiitem iiidifficulty iiiand iiidiscrimination/slope index iiiof iiithe iiitwo iiiinstruments iiiwith iii(t iii= iii3.52, iiidf iii= iii8, iiip iii< iii0.05) iiiand iii(t iii= iii3.26, iiidf = iii8, iiip iii< iii0.05) iiirespectively. iiiThe iiiauthor iiiconcluded iiithat iiithe iiideveloped iiiessay iiitest produced better iiiitem iiistatistics iiiestimates iiicompared iiito iiiNECO-MAT iii(essay) iiitest. iiiConsequently, iiiit iiiwas recommended iiithat iiipublic iiiexamining iiibodies iiiin iiisub-Sahara iiiAfrica iiishould iiiembrace iiian iiiapt polytomous iiimodel iiifor iiithe iicalibration iiof itheir itest items.